Physical properties of four ring-porous hardwood species: influence of wood rays on tangential and radial wood shrinkage - Elaieb, Mohamed Tahar; Shel, Foued; Jalleli, Mounir; Langbour, Patrick; Candelier, Kévin (Instituto de Ecología, A.C., 2019)
Some relationships between ray proportions, strength and shrinkage properties and basic density in hardwood species were highlighted. A better understanding of their relationships caused by the variation in moisture content in the hygroscopic domain could be a key factor in determining of wood stability properties and to determine the choice of a specific wood species according to its service life condition. The objectives of this study were (i) to determine the physical properties of various ring porous wood species (ii) and to evaluate the influence of wood rays (according to their proportions and volume) on physical properties of wood and more particularly on the Transverse Anisotropy Ratio for Shrinkage (TARS). This study focused on four ring-porous hardwood species; Castanea sativa, Quercus canariensis, Quercus petraea and Quercus robur, differing by the presence and abundance of their multiseriate wood rays. Basic densities, tangential shrinkages, radial shrinkages and the TARS of heartwood and sapwood from each wood species were determined. Wood-rays’ proportions and volume were measured by the image analysis method, and their influence on the last three shrinkages was investigated. A significant correlation between wood ray proportions, wood shrinkage values and basic density was observed.